The mysterious island - Mitchell, H. Q.; Verne, Jules (MM Publications London, 2006)
The Mysterious Island by Jules Verne is a classic adventure novel that tells the story of five castaways who are stranded on a remote island in the Pacific after escaping the American Civil War in a hot air balloon. The group, consisting of skilled and resourceful individuals, work together to survive and make the island habitable, using their scientific knowledge to create a new life. As they explore the island, they encounter strange phenomena and hidden secrets, leading to a thrilling discovery. The novel highlights themes of ingenuity, resilience, and the human spirit's capacity to overcome adversity.